Photocapacitance measurements in irradiated a-Si:H based detectors - Schwarz, R. (2014)
Photocapacitance measurements were performed on amorphous silicon p–i–n detectors before and after particle irradiation with 1.5 MeV 4 He+ ions. The spatial resolution across a degraded spot is similar to the one obtained in photocurrent scans and is of the order of the diameter of the scanning laser beam. We monitored the transient capacitance after applying short laser pulses to deduce trap energies of 0.64 eV. Photocapacitance measurements as a function of the applied bias, the measurement frequency up to 1 MHz, and the wavelength of laser light are discussed. The reduction in photocapacitance signal and the shift of the cut-off frequency after ion bombardment are correlated with the change in transport properties.